Growth Pattern Analysis of Whiteleg Shrimp (Litopenaeus vannamei) in an Intensive Aquaculture System at the Busmetik Pond, Sorong City, Southwest Papua - Saidin, Saidin; Supriatna, Iman; Rusli, Rusli (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2025)
Whiteleg shrimp (Litopenaeus vannamei) is a major aquaculture commodity that continues to be developed through intensive culture systems. This study aims to evaluate the growth patterns and survival rates of L. vannamei reared in an intensive aquaculture system at the Busmetik pond of the Sorong Marine and Fisheries Polytechnic during the 2021–2024 period. Observed parameters included average daily growth (ADG), average body weight (ABW), survival rate (SR), feed management practices, and water quality indicators. Data were analyzed using ANOVA and Kruskal-Wallis tests to identify interannual differences. Results revealed a consistent increase in SR, from 78.05% in 2021 to 91.7% in 2024, along with a steady improvement in shrimp length and weight, although the differences were not statistically significant (p > 0.05). Factors such as feed quality, feeding frequency, water pH and dissolved oxygen (DO), as well as disease control measures, were shown to influence culture performance. These findings suggest that integrated and adaptive management practices play a critical role in enhancing the growth efficiency and survival of L. vannamei in intensive aquaculture systems. Keywords: Litopenaeus vannamei, intensive culture, growth performance, survival rate, water quality